2015
DOI: 10.15844/pedneurbriefs-29-10-6
|View full text |Cite
|
Sign up to set email alerts
|

CSF Amino Acids, Pterins and Mechanism of the Ketogenic Diet

Abstract: Investigators from Hospital Sant Joan de Deu, Barcelona, Spain, studied the relationship between the etiology of refractory childhood epilepsy, CSF neurotransmitters, pterins, and amino acids, and response to a ketogenic diet in 60 patients with refractory epilepsy, 83% focal and 52% idiopathic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There have been several reports on changes in CSF levels of amino acids under KDT [ 31 , 32 ]; however, literature is limited on changes in serum amino acid levels in response to KDT. Millichap found that the only change in serum under KDT was an increased leucine level [ 15 , 33 ]. Levels of several amino acids, including phenylalanine, tyrosine, leucine/isoleucine, and methionine, were also significantly lower after 12 months of KDT.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on changes in CSF levels of amino acids under KDT [ 31 , 32 ]; however, literature is limited on changes in serum amino acid levels in response to KDT. Millichap found that the only change in serum under KDT was an increased leucine level [ 15 , 33 ]. Levels of several amino acids, including phenylalanine, tyrosine, leucine/isoleucine, and methionine, were also significantly lower after 12 months of KDT.…”
Section: Discussionmentioning
confidence: 99%